Real-world uptake of a tailored, text message pregnancy smoking cessation programme (MiQuit) when offered online - Emery, Joanne; Coleman, Tim; Sutton, Stephen; Cooper, Sue; Leonardi-Bee, Jo; Jones, Matthew; Naughton, Felix (2016)
Background: Prenatal smoking is a major public health concern and uptake of NHS cessation support is low in this group. Text message-based self-help is a promising intervention for this population but little is known about its likely real-world uptake, an essential parameter for estimating public health impact. Aims were to explore uptake (including cost) of a tailored, theory-guided, text message intervention for pregnant smokers (‘MiQuit’) when offered online. Methods: Links to a website providing MiQuit activation information (texting a shortcode) were advertised online on a cost-per-click basis for two commercial websites (Google AdWords, Facebook Ads) and free of charge for two smoking in pregnancy webpages (National Childbirth Trust, NHS Choices). Activations per advert click, per advert exposure and cost per activation were calculated. Findings: Low-visibility links on free-of-charge webpages generated few activations. For the commercial websites, cost per click was lower with Facebook but a higher proportion of Google advert clickers activated support (5.2% of 812 Google, 2.2% of 1889 Facebook), making their cost per activation very similar (£23.86 Google, £23.81 Facebook). Compared to participants of a prior MiQuit trial, those activating support online appeared more motivated (intended to quit smoking sooner) and those activating support via Google were earlier in pregnancy, with a sharp peak at 4-5 weeks gestation. Incremental costs per quitter were £746.19 (95% CI -£1,886.654 to £4,595.08) at the end of pregnancy and -£76.22 (-£2,790.33 to £3,844.02) when extended to mother’s lifetime. Discussion: Online advertisements are a feasible, potentially cost-saving method for engaging pregnant smokers in cessation support.